The “Double Trap” in China—Multiple Equilibria in Institutions and Income and their Causal Relationship - Linda Glawe; Helmut Wagner (Open Economies Review, 2022)
While institutions are said to be poor in China in cross-country comparison, recent research indicates that at the provincial level, institutional quality plays in fact an important role for the economic success of a province, municipality, or autonomous region in China. Our paper aims to add further arguments to this discussion by focusing on the concept of club convergence. In particular, we analyze whether institutional quality in low-income provincial level administrative divisions converges to the level experienced by relatively highly developed ones or whether there exist multiple institutional clubs over the period 1997–2007 by using the log t test proposed by Phillips and Sul (Econometrica 75(6):1771–1855, 43 ). Our findings indicate that there exist multiple institutional clubs within China, three rather small clubs which follow an above-average high institutional quality path and two clubs which find themselves on a relatively low institutional quality path and which together account for the majority of provinces and autonomous regions. Using the same methodology, we find that various members of the poor institutional clubs are additionally caught in a low-income trap. In a next step, we analyze the causal relationship between poor institutional traps and low-income traps in China by using a recursive bivariate probit model. We find evidence that institutional traps are important determinants of income traps, giving rise to the recently identified phenomenon of a 'double trap'. Finally, our findings indicate that human capital and urbanization are additional important determinants of income traps, while globalization is decisive for avoiding poor institutional traps.
Keywords: C23; O11; O43; O47; O5; R11; 330; Chinese economy; Club convergence; Income traps; Institutional quality; Log t test; Recursive bivariate probit estimation; Economic growth and development